HOW ORGANIZATIONAL CITIZENSHIP BEHAVIOUR ENHANCES TRANSFORMATIONAL LEADERSHIP: THE MEDIATING ROLES OF ORGANIZATIONAL LEARNING CULTURE AND WORK ENGAGEMENT IN HOSPITAL NURSE ON MALANG CITY - Wiayah, Nafahatul; Noermijati, Noermijati; Yulianti, Ida (Faculty of Administrative Science, Universitas Brawijaya, 2026)
This study examines the effect of transformational leadership on Organizational Citizenship Behavior (OCB), with organizational learning culture and work engagement as mediators. The study was conducted on nurses at Universitas Muhammadiyah Malang Hospital using a quantitative approach with questionnaire-based data. Data were analyzed using Partial Least Squares (PLS). The results reveal that transformational leadership has a positive and significant effect on OCB, organizational learning culture, and work engagement. Both mediating variables also significantly influence OCB and partially mediate the relationship between transformational leadership and OCB. These findings support Social Exchange Theory, highlighting the importance of reciprocal relationships in fostering extra-role behavior. Practically, enhancing OCB requires strengthening transformational leadership, organizational learning culture, and work engagement.